2017
DOI: 10.1101/180315
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights into autophagosome biogenesis from structural and biochemical analyses of the ATG2AWIPI4 complex

Abstract: Autophagy is an enigmatic cellular process in which double-membrane autophagic compartments form de novo adjacent to the ER, sequestering cytoplasmic contents within and delivering them to lysosomes. Expansion of the precursor membrane phagophore requires autophagy-related 2 (ATG2), which localizes to the phosphatidylinositol-3-phosphate (PI3P)-enriched ER-phagophore junction. We combined single-particle electron microscopy, chemical cross-linking coupled with mass spectrometry, and biochemical analyses to cha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 77 publications
(105 reference statements)
1
7
1
Order By: Relevance
“…These results are in contrast to the situation in yeast, where PAS localization of Atg18 depends on Atg2 [5,14,35]. Although ATG2s strongly interact with WDR45/WIPI4 [36][37][38], the requirement for ATG2s-WDR45 interaction in ATG2 localization to the isolation membrane remains unclear. Further studies are required to determine the precise hierarchy between ATG2s and WIPIs in mammals.…”
Section: Discussioncontrasting
confidence: 73%
See 4 more Smart Citations
“…These results are in contrast to the situation in yeast, where PAS localization of Atg18 depends on Atg2 [5,14,35]. Although ATG2s strongly interact with WDR45/WIPI4 [36][37][38], the requirement for ATG2s-WDR45 interaction in ATG2 localization to the isolation membrane remains unclear. Further studies are required to determine the precise hierarchy between ATG2s and WIPIs in mammals.…”
Section: Discussioncontrasting
confidence: 73%
“…During preparation of this manuscript, two groups reported the determination of the structure of the ATG2s-WIPI4 complex by single-particle electron microscopy and showed that the ATG2s have membrane-binding/tethering activity [37,38]. WIPI4 associates with a tip of ATG2, which adopts a rod shape.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations